Program Berkelanjutan Membantu Nagari Membangun di Nagari Sungai Kamuyang Kabupaten Lima Puluh Kota - Dwi Yuzaria; Rusda Khairati; Adisti Rastosari; A. Irzal Rias; Daz Edwiza (Warta Pengabdian Andalas, 2020)
The assisting Village development program is an activity carried out by the Andalas University Community Service Organization to Help Nagari improve the community economy in nagari Sungai Kamuyang, Luak District, Lima Puluh Kota Regency. It was implemented to help the Sungai Kamuyang village solve problems that hinder Nagari development. The problem faced by Nagari Sungai Kamuyang is that the utilization of natural and other resources is not optimal so that the poverty rate in this village is still quite high. Meanwhile, BUMNag which has been operating since 2017 have not been able to contribute to the original income of the village and foster economic activities for poverty alleviation. The general objective of this activity is to increase the capacity of BUMNag Sungai Kamuyang in developing its business to support the achievement of an independent Nagari, while the specific objective will be to map out the overall management problems of BUMNag Sungai Kamuyang, identify potential and strategic business units that can be implemented, compile business plans. to these potential and strategic business units and conduct business training and mentoring (training and mentoring) for the Sungai Kamuyang BUMNag Management Team in order to strengthen their capacity as a professional business entity. The solution offered is to carry out activities to increase the capacity of BUMNag businesses so that BUMNag become village business entities that are able to contribute to the village government.